EXPLORATION OF CHALLENGES BY KAFA TEACHERS IN IMPLEMENTING HIGHER-ORDER THINKING SKILLS (HOTS) IN PRIMARY SCHOOLS IN MALAYSIA - Nik Siti Nor Afida Ab Llah,; Halim Ismail, (Journal of Islamic, Social, Economics and Development, 2023)
The curriculum is the most important component in the educational field. The Ministry of Education in Malaysia has the best curricula, including the curriculum of Islamic Education that is parallel with the education of the 21st century. One of the curricula is integrating higher-order thinking skills (HOTS) in Islamic Education. Kelas Al-Quran and Fardu Ain (KAFA or Al-Quran and Fardu Ain Class) is part of Islamic Education which focuses on the teaching of basic Islamic teaching at public primary schools in Malaysia. KAFA is organised under the supervision of Jabatan Kemajuan Islam Malaysia (JAKIM or the Department of Islamic Development Malaysia). The study's primary purpose is to identify the challenges KAFA teachers face in implementing HOTS. Hence, interview sessions and document analysis collected qualitative data from KAFA teachers in one public primary school in Kelantan State. The study showed that KAFA teachers face different challenges in implementing HOTS. The results can inform schools and the educational system to prepare teachers with new strategies for implementing HOTS based on current situations and needs.